Is the Altman Z-Score Method Still Relevant in Predicting Bankruptct? A Study on PT. ESTIKA TATA TIARA TBK from 2019-2021 - Miyandini, Regita; Sirait, Ruth Angelin; Pangestu, Yogi; Chen, Levina (INTERNATIONAL JOURNAL OF TRENDS IN ACCOUNTING RESEARCH, 2023)
The purpose of this study is to examine how much the level of bankruptcy at PT Estika Tata Tiara Tbk in 2019 - 2021, the objects to be tested in this study focus more on the elements in the income statement and statement of financial position. This research uses descriptive research with secondary information obtained from the Annual Report of PT Estika Tata Tiara Tbk. The results of the research from 2019 - 2021 obtained results in 2019 Z Score of 1.81 in 2020 Z score of -7.62 and in 2021 obtained a Z Score of -7.47 which means that the company is predicted to go bankrupt